PTH-068 Tuberculosis in patients treated with vedolizumab: clinical trial and post-marketing case series. (17th June 2017) - Zerôncio, M; Blake, A; Rana-Khan, Q; Palo, W; Bhayat, F
Abstract : Introduction: The relative risk for tuberculosis (TB) can increase by ≤25 times with anti-tumour necrosis factor-alpha (TNFα) therapy. 1 Vedolizumab (VDZ) is a humanised monoclonal antibody that targets α4 β7 integrin and selectively blocks gut-specific lymphocyte trafficking. Gut selectivity may be associated with a lower risk of TB infection compared with anti-TNFα agents, which cause systemic immunosuppression. Here, we describe the frequency of TB with VDZ therapy in clinical trials and in the post-marketing (PM) setting. Method: Safety data from the GEMINI 1 and 2 studies (VDZ vs placebo, in ulcerative colitis [UC] and Crohn's disease [CD], respectively), the ongoing GEMINI open-label extension (OLE) study (VDZ only, both UC and CD; data cut-off: 21 May 2015) and PM data from the VDZ Global Safety Database (May 2014–31 August 2016) were reviewed. TB infections were classified according to the Medical Dictionary for Regulatory Activities. Results: In GEMINI 1, 2 and OLE, 6 TB events were reported in 5 patients (serious: n=5; non-serious: n=1; 1 patient experienced 2 events). In all patients, the events reported were mild to moderate in intensity, with no fatalities or extrapulmonary manifestations. TB was considered treatment-related in 3 patients. In 4 patients, TB resulted in discontinuation. One patient discontinued prior to TB onset, because of lack of treatment efficacy. In the context of 66 390 patient-years of post-marketing (PM) VDZ exposure, 5 patients reported TB events (serious: n=4; non-serious: n=1), none of which were fatal. Two patients had received anti-TNFα therapy prior to VDZ treatment. No concomitant/prior medication history was reported in the other 3 patients. At the time of reporting, 2 patients had discontinued VDZ treatment after diagnosis of TB, 2 had discontinued and later restarted, and 1 outcome was not reported (the product label recommends discontinuation until TB is resolved). The number of TB events reported in the PM setting relative to the total VDZ exposure in patient-years for each country was: US, 3/ 38, 102; France, 1/ 3, 471; and Germany, 1/ 8894. Clinical trial events occurred in countries where TB incidence is higher than in the US. Post marketing reports of TB from the US and Western Europe are likely to be due to greater VDZ exposure compared with countries that have a greater TB prevalence but no VDZ availability. Conclusion: The frequency of TB in VDZ clinical trials and the PM setting was low. Further insight on the frequency of TB in patients receiving VDZ will emerge from the OLE, ongoing observational studies and other real-world data. W. Palo is now at Abbvie Inc., North Chicago, IL, USA Reference: . Ali T, et al. Drug Health Patient Saf 2013;5:79. Disclosure of Interest: M. Zerôncio Conflict with: Abbvie, Janssen, Takeda, Apsen, Nestlé and Pfizer, Conflict with: advisory boards: Abbvie, Janssen, Takeda and UCB Biopharma; support for medical congresses: Abbvie, Janssen and Takeda., A Blake Conflict with: Takeda Development Centre Europe Ltd, Q Rana-Khan Conflict with: Takeda Pharmaceutical International AG Singapore, W Palo Conflict with: Takeda Development Centre Americas, Inc.; Abbvie, Inc., F Bhayat Conflict with: Takeda Development Centre Europe Ltd